Importance of the Second Opinion in Surgical Breast Pathology and Its Therapeutic Implications. (28th October 2020) - Ibarra, A; Baksai, K; Vial, M
Abstract: Introduction/Objective: Histopathological diagnosis determines surgical management and complementary therapies in patients with breast cancer. There has been reported significant diagnostic divergences, between 7.8 and 26%, and in tumor markers between 3.4 and 41%. We evaluate the agreement between diagnoses of general pathologists and specialists of our center, in which serious discrepancies could have therapeutic repercussions. Methods: Method: A retrospective study from 2012 to 2019. The cases were classified in benign and malignant. The atypical lesions were included with benign. Major disagreements were considered when there was a change in diagnosis from benign to malignant or vice versa, variation from intraepithelial to microinvasive carcinomas, infiltrating to intraductal carcinomas or vice versa. When necessary, we repeat routine stains and/or immunostains, or add new immunostains. Material: 295 cases. 294 women and 1 man. 228 biopsies and 67 immunostains of prognostic-predictive factors. Results: We found diagnostic differences in 46/295 cases (15.6%). Major discrepancies in 32 cases (10.8%). In morphological diagnoses 11/228 (4.8%) and in immunodeterminations 20/67 (29.9%). In diagnostic changes, they highlighted 3 cases of ductal carcinoma in situ (DCIS) to benign, 2 cases of benign lesions to DCIS, 1 benign to invasive ductal carcinoma (IDC), 1 DCIS to IDC and 1 IDC to DCIS. Conclusion: We found serious diagnostic divergences in 32 of 295 cases, 10.8%, which could have varied the therapeutic approach. In morphological interpretation 4.8% and in immunohistochemical results 29.9%. This should motivate multidisciplinary teams to routinely use the second opinion in surgical breast disease